Knowledge of Health Professionals on Cold Chain Management and Associated Factors in Ezha District, Gurage Zone, Ethiopia - Zeyneba Jemal Yassin; Habtamu Yimer Nega; Behailu Tariku Derseh; Yetnayet Sisay Yehuala; Abel Fekadu Dad (Scientifica)
Background. Maintaining quality of vaccines has been one of the main challenges of immunization programs in Africa including Ethiopia, and this could mainly be explained by health professional’s knowledge about cold chain management. There are limited studies done in Ethiopia linking the knowledge of health professionals on cold chain management, and that is why we needed to conduct this study. Methodology. Institution-based cross-sectional study was conducted among all available health professionals in selected health facilities (232 health professionals). Face-to-face interview using a semistructured questionnaire was conducted to collect required information from September to October 2016. Observational checklist was used to spot availability and functionality of refrigerators. Data entry and cleaning was done using Epi Info and exported to SPSS for analysis. A multivariable logistic regression model was fitted to identify factors associated with health professional’s knowledge about cold chain management. Result. The response rate was 92.43%, and 119 (51.3%; 95% CI; 44.9%, 57.6%) health professionals had a satisfactory knowledge about cold chain management. Being trained on immunization program (AOR = 5.1; 95% CI: 2.68, 10.13), having a work experience above six years (AOR = 2.1; 95% CI: 1.8, 4.15), using EPI guidelines (AOR = 2.58; 95% CI: 1.47, 5.57), and being a BSc nurse/health officer (AOR = 2.4; 95% CI: 1.47, 14.4) had got better knowledge on cold chain management. Conclusion. Health professionals working in the health centers and health posts had low knowledge on cold chain management. Longer work experience, in-service training, and using EPI guideline at work were factors that improved health professionals’ knowledge about a cold chain management, which needs to be maintained.